1992
DOI: 10.2214/ajr.159.1.1609697
|View full text |Cite
|
Sign up to set email alerts
|

Current role of cerebral angiography in the diagnosis of cerebrovascular diseases.

Abstract: PerspectiveThe role of cerebral angiography in the diagnosis of cerebrovascular disease is currently being questioned because of the increasing availability of MR angiography.The purpose of this essay is to place the use of cerebral angiography in perspective in light of these new developments.In patients with atherosclerotic cerebrovascuhar disease, MR angiography can almost entirely supplant cerebral angiography as a screening procedure in the evaluation of the carotid bifurcation. However, detection of "pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…TOF MRA has been proven useful for visualizing occlusions or severe stenoses of major head and neck vessels [38]. In the present study, with as little as 20 min prolongation of the MR time, MRA identified and characterized vascular occlusions and stenoses well enough to obviate the need for catheter exams in 1 of 5 cases and to help direct the angiogram in the other 4.…”
Section: Discussionsupporting
confidence: 48%
“…TOF MRA has been proven useful for visualizing occlusions or severe stenoses of major head and neck vessels [38]. In the present study, with as little as 20 min prolongation of the MR time, MRA identified and characterized vascular occlusions and stenoses well enough to obviate the need for catheter exams in 1 of 5 cases and to help direct the angiogram in the other 4.…”
Section: Discussionsupporting
confidence: 48%
“…Iv tpa is the fastest way to initiate therapy in hyperacute ischaemic stroke, but its efficacy in patients with lvo is questionable: it is well documented that Iv tpa has limited efficacy in recanalising lvo [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (see table 2) and recanalisation is a strong predictor of good outcome 7,9,10,11,[22][23][24]34 . the larger clot volume ening endovascular therapy 6 .…”
Section: Recanalisation and Clinical Outcomes With IV Tpamentioning
confidence: 99%
“…The gold standard technique for evaluating arterial dissections is catheter digital subtraction angiography (DSA). The benefi ts of this technique include higher sensitivity for detecting small intimal fl aps, intraluminal thrombus, intracranial extension, and the presence of aneurysms or other vascular anomalies [32,33]. The major drawback, especially in the sCAD population, is the risk of vessel dissection, which may be higher if there is an underlying collagen abnormality, and this has greatly limited its use in diagnosing this disease.…”
Section: Diagnosismentioning
confidence: 99%